Stakeholder theory and organizational ethics - Phillips, Robert, 1968- 4 0 16; 5 (San Francisco : Berrett-Koehler, 2003)
Robert Phillips provides a detailed analysis of the current controversies in stakeholder theory and examines several controversial candidates for stakeholder status - including competitors, activists, and the natural environment - and provides a means for determining who are and are not stakeholders and why.--BOOK JACKET.
Stakeholder theory and organizational dogma -- The limits of stakeholder theory -- Why organizational ethics? -- Stakeholder theory and its critics -- A principle of stakeholder fairness -- Stakeholder legitimacy -- Stakeholder identity -- Stakeholder theory in practice.
Includes bibliographical references (p. 180-190) and index
Keywords: 2 -- 0; 6; Corporate governance.;Business ethics. -- 20; 20; 2